Isso é uma guerra: a produção de sentido de jovens da periferia de Fortaleza sobre os homicídios juvenis - Cavalcante, Ana Jéssica de Lima (2018)
The phenomenon of homicides can be considered a sociological issue. Many official sources data and university research had turned to this question, but this phenomenon still isn’t seen as a social problem, once there is no implication of society and the State for its reduction. In the psychology science field, this matter still has incipient literature. Homicides are treated just as numbers by a large part of the population, especially those that occur against young people living on the city's fringe. The ways how the societies deal with the transformations of the individual, caused by the age group, are varied and can thus suffer modifications in time and space. Young people are seen socially as producers of violence, especially blacks and residents of peripheral regions of large urban centers. However, what the main data about urban violence point to us is that young black man from periphery is the priority target of various violences. Fortaleza is at the top of the statistics in regard to homicides of young people and adolescents. In 2016, the Committee for the Prevention of Homicide in Adolescence of State of Ceará was created, which promoted a research to know the profile of the young people killed. It was found that in 5 years in Fortaleza there were 2,693 homicides in the age group of 10 to 19 years. Therefore, the aim of this master thesis was to analyze the meanings constructed by young people in situations of social vulnerability, in relation to juvenile homicides, starting from the following question: how young people who are in conditions of social vulnerabilities similar to those pointed out by the statistics produce meaning about juvenile homicides? To achieve this, we use a qualitative approach that includes a historical and particular perspective of the participants. As a methodological procedure, we chose Life Story Narratives. The locus of the Research was the four territories that had the highest homicide rates in the year 2016, which are: Bom Jardim, Jangurussu, Barra do Ceará and Vicente Pizón. According to data of the Committee for the Prevention of Homicide in Adolescence of State of Ceará, the four neighborhoods totaled 356 homicides in relation to the general population. Thus, young people between the ages of 15 and 29, who showed availability and a profile of living conditions close to those that are the target of State violence, participated in the study. The analysis of the corpus was made under Cultural Historical perspective, through an interpretative analysis. This approach allowed the understanding of meanings and senses produced by the youth and became possible a subjective reconstruction about the phenomenon of homicides. The theoretical analytical categories who guided this study was: youth, racism, intersectionality, necropolitics, violence and homicides. These were articulated with empirical categories, that we found from the analysis of narrative interviews of the young, which are: territory, risk and protection, killable subject, resistances. We defined as unit of analysis the discursive productions of the narrative interviews conducted with the participants. The challenge of this study is to give visibility to the issue of Homicide against young people as a social problem, on which society and the State should become implicated in its transformation, in a construction taking into account young people and with them find the ways for their coping and overcoming.